2010
DOI: 10.4269/ajtmh.2010.09-0235
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Under-Reporting of Visceral Leishmaniasis Cases in Bihar, India

Abstract: Abstract.We estimated the level of under-reporting of visceral leishmaniasis (VL) cases by comparing the actual reported cases with those expected as estimated using age-and sex-stratified incidence proportions obtained in a cohort of 31,324 persons. The average incidence proportion of VL cases in study population was 5.7/1,000 (95% confidence interval [CI] = 4.88-6.54) and 1.09/1,000 persons (95% CI = 0.99-1.20) based on the reported cases in two primary health centers. The overall magnitude of VL cases not r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
74
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 6 publications
1
74
0
1
Order By: Relevance
“…In this connection it is important to note that infection rates in human that act as reservoirs for VL transmission (e.g., post-kala-azar dermal leishmaniasis, P�DL) are signi�cantly higher, as observed in the four main states (e.g., Bihar, Jharkhand, West Bengal, and Uttar Pradesh) of India [6]. Previous study has shown the conspicuous increase of visceral leishmaniasis cases in India, especially in Bihar [45,46]. One of the factors for increasing trend of the disease could be due to the increase in reporting of kala-azar cases at public health centers (PHCs) due to massive kala-azar awareness programme undertaken by health agencies and Government of India.…”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this connection it is important to note that infection rates in human that act as reservoirs for VL transmission (e.g., post-kala-azar dermal leishmaniasis, P�DL) are signi�cantly higher, as observed in the four main states (e.g., Bihar, Jharkhand, West Bengal, and Uttar Pradesh) of India [6]. Previous study has shown the conspicuous increase of visceral leishmaniasis cases in India, especially in Bihar [45,46]. One of the factors for increasing trend of the disease could be due to the increase in reporting of kala-azar cases at public health centers (PHCs) due to massive kala-azar awareness programme undertaken by health agencies and Government of India.…”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
“…However, there is a great need to rigorously implement control interventions in those areas where the disease continues to be endemic, as documented by the latest available data of VL on a national scale [45,46,51,52]. In fact, north Bihar (India) that covers 31 districts along the Ganges River is characterized by high population densities, suitable climate, and large areas that are favourable for proliferation of P. argentipes breeding.…”
Section: Future Outlook and Conclusionmentioning
confidence: 99%
“…3 A similar and more recent study put underreporting of VL at 4.74 and 3.51 times in males and females, respectively, in Lalganj and Goraul villages in Bihar, India. 4 Thus, it is generally believed that the current estimates of disease burden may not reflect the true impact of the diseases.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of Indian VL cases occur in the northeastern states, predominantly in Bihar (3,4). The numbers of VL cases reported in India are based on passive case reporting, and therefore may be an underestimation (2,5); however, regardless, advances in VL diagnostic tests and improved treatment modalities have ensured that the number of deaths due to VL in India has gradually decreased over the past 5 y (6).…”
mentioning
confidence: 99%